ROLE OF GOOD CORPORATE GOVERNANCE AS A MANIFESTATION OF ORGANIZATIONAL DEMOCRACY - Fransiskus Xaverius Candra Gunawan (Dinasti Publisher, 2022)
This research is a form of conceptual idea that examines the impact of dynamic changes on increasingly fierce business competition and company sustainability. The concept of corporate management presented by Good Corporate Governance (GCG) is a wise solution that companies need to consider to answer the challenges of these changes, where the existence of clean and healthy company management and superior human resources are important company assets that need to be improved. The research method uses qualitative research with a descriptive qualitative approach in the form of critical ideas sourced from national literature, international journals, and research libraries. The results of the study conclude that the role of Good Corporate Governance (GCG) as a manifestation of organizational democracy can improve employee morale and work ethic which is the company's competitive advantage. In addition, the existence of a space for the active participation of stakeholders is the most important part of the practice of Good Corporate Governance (GCG).